(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Children, one of the most vulnerable part of the population, face unusually high health risks as they grow. Children are the promise and future of every nation and the core of development. But it has been observed that even after so many efforts by governments of developing countries we are far behind to achieve hundred percent health care utilization by under-five population. Keeping this in view, this study was conducted to find out any correlation in-between child mortality of under-five years of age with health care utilization and place of residence. using verbal autopsy as a tool in Dehradun. Methodology: The survey was done on all the houses of the deceased children residing in our field practice areas by visiting their houses. Results: Among the 83 deaths reported, 38 received no treatment, 10 were treated by quakes, 19 and 16 under five – children were treated in government and private hospital respectively. Conclusion: Our study shows that by utilization of health care facilities we can remarkably reduce under five mortality.